The Representation of People with Disabilities in Jordanian Basic School Textbooks - Abu-Hamour, Bashir; Al-Hmouz, Hanan; Aljarrah, Abdallah (DIRASAT: EDUCATIONAL SCIENCES, 2019)
The appropriate representation of people with disabilities (PWDs) in basic school textbooks may be used to facilitate the movement toward inclusive education; and enforce the Jordanian Law on the Rights of PWDs for the year of 2017. The present study aims at examine how basic school textbooks that are published in Jordan approach subjects about PWDs. 37 basic school textbooks (grade 1 to grade 10) that cover subjects of Arabic Language and "Social, Citizenship, and Civic" Education, published by the Ministry of Education in Jordan are examined with respect to their method of addressing PWDs. The researchers use the content analysis (texts and images) method in order to facilitate this investigation. Results indicate that PWDs are rarely represented, and the Law of disability was largely ignored in the Jordanian basic school textbooks. Recommendations are presented for improving the integration of PWDs subjects into textbooks